The Effect of Compensation and Rewards on Job Satisfaction through Punishment as an Intervening Variable - Rahadi, Dedi Rianto; Prastiani, Elsadai Dwi; Fajri, Faizah Meyliana; Alfinandita, Intan Maya Zena (LPPM Universitas Pelita Bangsa, 2024)
This study aims to analyze the effect of compensation and rewards on job satisfaction throughpunishment as an intervening variable. This research applies the Structural Equation Modeling (SEM) - Partial Least Squares (PLS) analysis technique using the Smart PLS Version 3 tool in processing data obtained through distributing questionnaires to 314 employees of PT Suka Sukaku. The results showed that punishment has no significant effect on job satisfaction, giving fair awards has a positive impact on employee job satisfaction, compensation has a significant effect on job satisfaction, compensation has a significant effect on punishment, awards have a significant effect on job satisfaction, compensation has a significant effect on job satisfaction through punishment and awards have a significant effect on job satisfaction through punishment